Improving Troponin Turnaround Time to Enhance Early Cardiac Event Detection: A Quality Improvement Project - Hatch, Christie J. (My University, 2026)
Background & Purpose Troponin, a cardiac biomarker that helps to diagnose myocardial injury in the setting of a heart attack, is an essential tool used by providers early on in a myocardial infarction (MI). The current guidelines recommend trending this lab value a minimum of twice at standard intervals after the suspected cardiac event. The American College of Cardiology has several recommendations for chest pain centers to follow in order to reduce door-to-reperfusion times for patients who require intervention for their MI, one of which relates to the amount of time for the troponin lab value to result (which should be less than or equal to 60 minutes from patient arrival). Prior to this initiative, at an acute care hospital, which is an ACC-accredited facility, 12% of the troponin labs resulted within the goal timeframe. Patients at risk for acute coronary syndrome (ACS) require efficient testing to diagnose and treat their condition. With a median turnaround time of 95 minutes (prior to this initiative), patients having an MI are at risk of further injury. The hospital ED put together a project team to oversee a quality improvement project aimed at increasing the number of troponin results that meet the goal timeframe. Methods: This QI project used a PDSA format, with several phases of introduction during implementation. Results: Improvement from 12% to 22% of troponin results met goal during the 12-week implementation, with the biggest increase being the week that phlebotomists were added. Conclusion: As a result, additional phlebotomy staff will be requested in the ED to help with lab draw compliance and timely results.
Keywords: troponin, chest pain, cardiac, turnaround time, door-to-result, PDSA